Greenhouse gases produced by primary schools in Belén, Heredia, Costa Rica. (UNED Research Journal, 2015)
There is no published information on greenhouse gas emision in public schools of Costa Rica. Using as reference the national voluntary standard INTE / ISO 12-01-06: 2011 I measured emissions in three primary schools: Escuela España, Escuela Fidel Chaves and Escuela Manuel Pilar Zumbado González. The estimates were made using emission factors from the National Meteorological Institute in 2013 as the reference year. The WARM model was used for removal emissions. The main sources were CH4 generation caused by the production of solid waste (69% in España, 70% in the Chavez and 67% in Zumbado) and wastewater management (28.4% in España, 28.8% in Chaves and 27.6% in Zumbado). These were followed by the generation of CO2e by electricity consumption (1.97% in the España, 1.83 in Chaves and 3.1% in Zumbado). The three schools show a similar trend in sources and emissions. This similarity suggests that the management of GHG emissions should focus on these sources in public primary schools in urban areas.
Keywords: Climate change; public schools; Voluntary national standard.